Rapid Plasma Exsolution from an A‐site Deficient Perovskite Oxide at Room Temperature. Issue 45 (3rd October 2022) - Khalid, Hessan; Haq, Atta ul; Alessi, Bruno; Wu, Ji; Savaniu, Cristian D.; Kousi, Kalliopi; Metcalfe, Ian S.; Parker, Stephen C.; Irvine, John T. S.; Maguire, Paul; Papaioannou, Evangelos I.; Mariotti, Davide
Abstract: High‐performance nanoparticle platforms can drive catalysis progress to new horizons, delivering environmental and energy targets. Nanoparticle exsolution offers unprecedented opportunities that are limited by current demanding process conditions. Unraveling new exsolution pathways, particularly at low‐temperatures, represents an important milestone that will enable improved sustainable synthetic route, more control of catalysis microstructure as well as new application opportunities. Herein it is demonstrated that plasma direct exsolution at room temperature represents just such a step change in the synthesis. Moreover, the factors that most affect the exsolution process are identified. It is shown that the surface defects produced initiate exsolution under a brief ion bombardment of an argon low‐pressure and low‐temperature plasma. This results in controlled nanoparticles with diameters ≈19–22 nm with very high number densities thus creating a highly active catalytic material for CO oxidation which rivals traditionally created exsolved samples. Abstract : Direct low‐temperature plasma exsolution is demonstrated for the first time, where oxygen defects are promoted by physical means. Exsolution is observed with an argon low‐pressure low‐temperature plasma, achieving large particle densities. These results pave the way to new research directions to understand the fundamentals of direct plasma exsolution, exsolution with new materials and chemistries, as well as new application avenues.